2002
DOI: 10.1097/00004010-200207000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Diffusion Patterns for Complex Health Care Innovations

Abstract: Why are some less solidly supported health care innovations widely adopted while others with apparently stronger scientific support remain underused? Drawing on four case studies, the authors argue that the way in which the distribution of benefits and risks map onto the interests, values, and power distribution of the adopting system is critical to understanding how innovations diffuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
309
1
11

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(329 citation statements)
references
References 9 publications
8
309
1
11
Order By: Relevance
“…For example, call centre staff typically have an arrangement with the families of their clients as to who will be called, under what circumstances and what actions will be taken when an alarm is triggered. Interviews with people involved in the development of ALT devices and provision of services in the UK (for a full account see Sugarhood et al 2014) illustrated that for the technology to 'work' effectively, this network of professional and lay carers (the technology's 'soft periphery' (Denis et al 2002)) must be adaptable to the needs of the client, though we found that this did not always occur in practice.…”
Section: Assisted Living Technologies and Servicesmentioning
confidence: 83%
“…For example, call centre staff typically have an arrangement with the families of their clients as to who will be called, under what circumstances and what actions will be taken when an alarm is triggered. Interviews with people involved in the development of ALT devices and provision of services in the UK (for a full account see Sugarhood et al 2014) illustrated that for the technology to 'work' effectively, this network of professional and lay carers (the technology's 'soft periphery' (Denis et al 2002)) must be adaptable to the needs of the client, though we found that this did not always occur in practice.…”
Section: Assisted Living Technologies and Servicesmentioning
confidence: 83%
“…Perhaps evidence is not enough to convince us-as many sociologists have pointed out. Rogers' diffusion of innovations theory explains that innovations that depart from centuries-old traditions can be slow to take hold, and require innovators to spread them [49,50]. In Kuhn's theory of paradigm shifts, old models that no longer adequately account for anomalies are slowly replaced with new [51].…”
Section: Eliciting Values and Preferencesmentioning
confidence: 99%
“…Previous studies have shown this to be an important factor in the uptake of innovation in health services (see for example: Denis et al, 2002), and in this CAMHS team the purposeful presentation of this girl's critical juncture helped the larger, planned, effort of promoting system change by connecting with practitioners' beliefs. In terms of actors and their goals (Capoccia and Kelemen, 2007), the elevation of the girl's case into the meso-level was a purposeful act on the part of those concerned to introduce uncertainty in the service of organisational development.…”
Section: Aim Design and Methodsmentioning
confidence: 92%